The impact of Islamic work ethic and perceived organizational support on organizational commitment of Islamic bank employees: The role of felt obligation as mediator / Ahmed Raja Ahmed Haj Ali - Ahmed Raja , Ahmed Haj Ali (2019)
In the more rapidly developing Asian and emerging markets, the Malaysian Islamic banking industry has expanded remarkably, playing a pivotal role in supporting the evolution and sustainability of the Malaysian economy. Although, the Islamic banking system in Malaysia is inclusive of manifold opportunities, it has its own substantial challenges too. For example, employees are required to be completely aligned with the Islamic banks’ philosophy i.e. mission, goals and objectives. The banks also require high quality services which impose a high workload on the bank’s employees. The misconception of Islamic banking amongst Muslim employees can also result in the decrease of their organizational commitment, causing serious doubts and reservations among Islamic banks’ staff when fulfilling obligations. The present research explores and examines the factors that may have an impact on employees’ organizational commitment in the context of the Islamic banking industry in Malaysia. As such, this empirical study examines the potential impact of Islamic work ethics and perceived organizational support on Muslim employees’ organizational commitment, and assesses the mediating role of felt obligation. Hence, a theoretical framework was developed from past literature. Through a self-administrated questionnaire, 291 usable responses were obtained from Islamic Banking employees in Klang Valley. The primary data acquired by the research instrument was prepared using SPSS. SEM method was performed using AMOS tool for data analysis. A valid measurement model based on goodness-of fit indices was achieved and the full structural model was also tested. Accordingly, the findings of the structural model revealed that out of the seven hypotheses that were postulated earlier in the research model, six were supported. The final results of this research show that organizational commitment appeared to have been directly and indirectly influenced by all constructs, except the structural path between the IWE and organizational commitment. Further, it was revealed that felt obligation partially mediated the relationship between POS and organizational commitment, while it was a full mediator in the relationship between IWE and organizational commitment. The research conceptual framework is a unique application for the progression of the social behavior theories, concluded with several clear suggestions for future studies. Finally, the study results should give HR, managers, and decision-makers in Islamic banks a better insight to enhance their employees’ positive perception and moral conducts towards their workplace. The study findings can also be a valuable asset to justify their need to retain and develop their experienced employees and get them more involved with the Islamic banking approach.